Feminist Jurisprudence, Women Ulama and Iftā in Indonesia - Fatima Seedat (African Journal of Gender and Religion (AJGR))
Eight years ago a group of Indonesian women scholars who constituted themselves as ‘women ulama’ claimed the epistemic authority to pronounce on matters of Islamic law, and enacted it by issuing three collective fatwas. Six years later they repeated this process and issued four more fatwas. How should we read this development, in terms of the Muslim women’s movement, and the growth and development of Islamic law? Recognising the fatwa as the fundamental element of Islamic legal thought, the work of KUPI continues and expands modern processes of collective fatwa making. Significantly KUPI also add a framework derived from women’s experiences of the law; namely attention to maʿrūf (goodness), mubādalah (hermeneutics of reciprocity), and hakiki (substantive or true) justice. Even as Muslim women advance innovative readings of classical Islamic law and its legal processes, feminism remains entwined in a colonial history that is difficult to lose. And so the feminist associations of the work of the KUPI remain muted for now. Their achievements, however, must be announced and celebrated.